2018
DOI: 10.4066/biomedicalresearch.29-17-3138
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal factors influencing mother-to-child HBV transmission

Abstract: Background: Chronic hepatitis B virus (HBV) infection remains a key public health problem. In China, mother-to-child transmission is recognized as the major transmission pathway. The exact mechanism by which HBV enters the fetus through the maternal placenta is unclear, hampering the development of preventative interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Also, it is still unclear whether this difference could have been due to a higher risk of perinatal transmission of HBV in males. Some studies have reported that the male sex was associated with a higher risk of perinatal transmission of HBV (Li et al, 2014;Siakwa et al, 2016), while other studies have found no difference in HBV transmission between the sexes in infants (Agbede et al, 2007;Chen et al, 2018a;Zhang et al, 2014). Sexual HBV transmission is a plausible explanation for the higher risk of HBsAg among males, since most of the male participants reported practicing anal sex, which has also been associated with HBsAg positivity (Lange et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is still unclear whether this difference could have been due to a higher risk of perinatal transmission of HBV in males. Some studies have reported that the male sex was associated with a higher risk of perinatal transmission of HBV (Li et al, 2014;Siakwa et al, 2016), while other studies have found no difference in HBV transmission between the sexes in infants (Agbede et al, 2007;Chen et al, 2018a;Zhang et al, 2014). Sexual HBV transmission is a plausible explanation for the higher risk of HBsAg among males, since most of the male participants reported practicing anal sex, which has also been associated with HBsAg positivity (Lange et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Density is an important parameter to measure performance and influences the mechanical properties of bamboo [20]. Fourier transform infrared spectroscopy (VERTEX 80V infrared spectrometer, Bruker, Karlsruhe, Germany) was used to study the gradient changes in its chemical properties.…”
Section: Density and Vascular Bundle Distributionmentioning
confidence: 99%
“…Density is an important parameter to measure performance and influences the mechanical properties of bamboo [20].…”
Section: Density and Vascular Bundle Distributionmentioning
confidence: 99%